Communicative Responses to the Painful Self-Disclosures of Familial and Non-Familial Older Adults. (October 2013) - Fowler, Craig; Soliz, Jordan
Data from 365 college students were used to assess young adults' communicative responses to older persons' painful self-disclosures (PSDs). Coupland, Coupland, and Giles (1991) proposed that recipients of PSD may respond to such disclosures via a variety of "next moves." These responses may broadly be considered to reflect forms of pro-social engagement, passive disengagement, and active disengagement. We investigated whether young adults' tendency to use certain responses to PSD were influenced by their affective reactions to PSD, their communicative background and characteristics, and the sociorelational context of the encounter in which PSD occurred. Results are discussed with respect to their implications for intergenerational interaction, and interpreted through the lens of communication accommodation theory.